2020
DOI: 10.1177/0011128720940963
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Differences in Homicide Incarceration Rates by Immigration Status: A Comparison in Texas

Abstract: Research addressing the purported relationship between immigration and crime remains popular, but some gaps remain under-explored. One important gap involves disentangling differences in crime and punishment by immigrant status, as measured across different definitions of immigration status and in relation to U.S. natives, at the individual level. Using data from Texas, results show that native-born U.S. citizens are incarcerated for homicide at higher rates than almost all immigrant groups. While the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The analysis presented here of a sample of individuals incarcerated for homicide provides additional evidence to support previous research on differences in rates of offending (Bersani & Piquero, 2017;Bersani et al, 2018) and work showing that rates of incarceration for homicide vary significantly by immigration status (Orrick et al, 2021). Findings here go further to support the idea that differences based on immigration status in rates of previous offending are present, even among our subsample of individuals incarcerated for homicide.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The analysis presented here of a sample of individuals incarcerated for homicide provides additional evidence to support previous research on differences in rates of offending (Bersani & Piquero, 2017;Bersani et al, 2018) and work showing that rates of incarceration for homicide vary significantly by immigration status (Orrick et al, 2021). Findings here go further to support the idea that differences based on immigration status in rates of previous offending are present, even among our subsample of individuals incarcerated for homicide.…”
Section: Discussionsupporting
confidence: 85%
“…We do not claim that those who have been confirmed by ICE as foreign citizens are unauthorized; however, it is among this group that estimates of undocumented immigrants are subsequently derived. Using similar data, Orrick et al (2021) reported that approximately two-thirds of the identified foreign citizens in their sample were undocumented, suggesting that many undocumented individuals may be present in our sample. However, this indicator of immigration status is not publicly available from TDCJ at the individual-level.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Yet prior research on citizen-noncitizen disparity in punishment is limited in that it typically examines one race/ethnicity (Ulmer and Parker 2020), noncitizens as one group (Light 2014; Wu and D’Angelo 2014), or only drug offenses (Demuth 2002; Hartley and Armendariz 2011; Iles and Adegun 2018; Logue 2009). Furthermore, in a study that examined homicide offenses in Texas, Orrick et al (2021) found that noncitizens are incarcerated less frequently than U.S. citizens, adding to the uncertainty as to whether there is a noncitizen penalty for all offense types. Although evidence of sentencing disparity between citizens and noncitizens has accumulated in recent years, it is unclear which noncitizen groups are most severely sentenced, and for which offense types.…”
Section: Previous Researchmentioning
confidence: 99%